Spontaneous absence-like activity in Wistar rats: Behavioral and electrographic characteristics and the effects of antiepileptic drugs (Acta Scientiarum. Biological Sciences, 2014)
Current investigation describes the behavioral and electrographic characteristics of spontaneous absence-like seizures identified in Wistar rats (referred to here as FMUSP-rats, after the Faculty of Medicine, University of São Paulo, São Paulo State, Brazil), and characterized by spike-wave discharges (SWDs) in the neocortex and the hippocampus. After consanguineous crossing directed to an increased incidence of seizures, the latter were observed in almost all F9 offspring. FMUSP-rat seizures are expressed as immobility and concomitant SWDs, oscillating between 7.5 and 12 Hz in the frontoparietal cortex and the hippocampus. Behaviorally, they are mainly associated with clonic movements of the eyes, rostrum and vibrissae, the latter ranging between 1 and 70 seconds and occur at a rate of up to 229 per hour. Systemic injections of ethosuximide (0, 25, 50, 100, 250 mg kg-1) and of diazepam (15 mg kg-1) increased the latency for the first seizure and reduced both the hourly incidence of SWD bursts and their mean duration. Carbamazepine (30 mg kg-1) injections increased both the incidence and duration of the SWDs, leaving the latency for the first seizure unchanged. Comparisons between FMUSP-rats and well-established genetic models of absence seizures data indicated that the animals described herein might contribute towards studies on the neurological condition under analysis.